P12.09 Clinical features and management of normal pressure hydrocephalus associated with non-obstructive vestibular schwannoma. (9th September 2021) - Redaelli, V; Gaviani, P; Simonetti, G; Botturi, A G; Marchetti, M; Broggi, M A; Silvani, A
Abstract: BACKGROUND: Some (elderly) patients present a communicating (normal pressure) hydrocephalus (NPH) in association with or secondary to vestibular schwannoma (VS). We aim to investigate the usefulness ventriculo-peritoneal shunt (VPS) without tumor removal. MATERIALS AND METHODS: 8 patients aged from 50 to 78 years received both diagnosis of VS (mean maximum diameter 21 mm, range 13–28 mm) and NPH. None presented the classical Hakim's triad. They presented isolated ataxia with gait impairment and loss of equilibrium. It was hard to distinguish if these symptoms were due to NPH or to VIII cranial nerve compression. They underwent TAP test, through a lumbar puncture with a very slow whithdrawal of at least 30 ml of cerebrospinal fluid (CSF). RESULTS: None of the 8 patients presented improvement after lumbar puncture. Despite this, we decided to proceed with VPS in 4 patients because of a high risk of falls.... All these 4 patients showed clinical improvement after VPS.. The VS were treated as follows: 4 surgery, 2 radiosurgery, 2 observation. CONCLUSIONS: Although some authors indicate VS removal as the best option to improve also NPH symptoms, some patients present high risk of falls in the presence of a small VS. These clinical features are more likely to be relayed related to NPH instead of VS.. VPS carries lower postoperative risks compared to VS removal. For this reason, VPS has to be considered, even without a positive response to a TAP test, as a good alternative to improve quality of life in patient affected by NPH associated with VS.